Should Quality of Glycemic Control Guide Dental Implant Therapy in Patients with Diabetes? Focus on: Peri-Implant Diseases - Aldahlawi S (Clinical, Cosmetic and Investigational Dentistry, 2021)
Salwa Aldahlawi,1 Dalia Nourah,1 Sebastiano Andreana2 1Department of Basic and Clinical Oral Sciences, Faculty of Dentistry, Umm Al-Qura University, Makkah, Saudi Arabia; 2School of Dental Medicine, University at Buffalo, Buffalo, NY, USACorrespondence: Salwa AldahlawiFaculty of Dentistry, Umm Al-Qura University, Taif Road, Al-abdiyyah, Makkah City, Saudi ArabiaTel +966 500559365Fax +966 125274203Email Sadahlaawi@uqu.edu.saBackground and Aim: Traditionally patients with metabolic conditions such as diabetes mellitus are considered not suitable candidates for dental implant therapy due to increased risk of infection, impaired bone healing or the potential for vascular complications. Peri-implantitis as the more progressive form of peri-implant disease involves bone loss and estimated to occur in nearly half of all implant cases long-term. Despite extensive research on association of hyperglycemia with dental implants in preclinical and animal models, translational effort to clinical practice is hampered by discrepancies in reported outcome indicators for peri-implantitis in patients with a spectrum of glycemic profiles. This review aims to evaluate clinical evidence for peri-implant disease in metabolically compromised patients and in particular in patients with poorly-controlled diabetes in order to inform clinical management of peri-implant disease.Materials and Methods: A comprehensive literature review was performed utilizing PubMed database and using the key word ‘diabetes’ combined with “dental implant” or “Periimplantitis” or/and “Preimplant disease”.Results: Clinical studies with follow up more than 1year, systematic review and meta-analysis that evaluated peri-implant disease in diabetic patients in relation to glycemic control were taken into consideration in this review.Conclusion: Studies reported conflicting results regarding the long-term effect of diabetes on peri-implant health regardless of the level glycemic control. Therefore, interpretation of finding and relevance to clinical practise should be considered on individual bases.Keywords: dental implant, diabetes, glycemic control, osseointegration